Student’s Psychological Flexibility Based on Gender Differences in Indonesia - Alrefi, Alrefi; Nurihsan, Juntika; Rusmana, Nandang; Nurhudaya, Nurhudaya (International Conference on Elementary Education, 2020)
The purpose of this study is to determine the level of psychological flexibility of Tenth Grade Students of Senior High School and Vocational School based on gender differences. Research activities are conducted in the even semester of the 2018/2019 school year. This research uses a quantitative approach with a survey method. The data measurement tool is a questionnaire in the form of a scale developed by Rolffs based on psychological flexibility indicators. The study participants were Tenth Grade Students of Daarut Tauhid Boarding School Bandung Vocational High School 2018/2019, totaling 116 participants consisting of 58 men and 58 women. The result showed in general psychological flexibility in male students is higher than the psychological flexibility of female stdents. As for the general description obtained general psychological flexibility of students that is about 14 (12%) students have psychological flexibility at a high level, 75 people (65%) are at a moderate level, and 27 people (23%) are at a low level. This data provides a strong position that efforts to develop psychological flexibility in students become an important issue and become the main goal with the need for guidance and counseling services